Chronology of the HIV-1CRF07BC expansion in East Asia - Tee, K.K.; Pybus, O.G.; Liao, H.; Uenishi, R.; Hase, S.; Kamarulzaman, A.; Li, X.J.; Takebe, Y. (2008)
The HIV-1 epidemic among injecting drug users (IDU) in Taiwan is caused primarily by CRF07BC infections. Evolutionary analyses, which utilize outgroup reference strains from northwestern China (Xinjiang), reveal that CRF07BC was introduced into southern Taiwan in 1998-2001 and spread to central-northern Taiwan in 2001-2003, causing the largest HIV/AIDS epidemic in Taiwan. The separate introduction of CRF07BC into Xinjiang occurred in 1992-1995. This study illustrates the temporal dynamics of CRF07BC spread among IDU across east Asia.